Mathematics of computation. Volume 65, Number 214 , 1996 - American Mathematical Society (American Mathematical Society, 2009)
Contents of Volume 65, Number 214 View front matter and back matter from the print issue of this journal View front and back matter from the print issue All articles in this issue are available free of charge Interior penalty preconditioners for mixed finite element approximations of elliptic problems Torgeir Rusten; Panayot S. Vassilevski; Ragnar Winther Math. Comp. 65 (1996), 447-466. Abstract, references and article information Retrieve article in: PDF